2017
DOI: 10.1111/1365-2664.12865
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐corridor solutions for climate‐vulnerable plant species groups in South Korea

Abstract: 1.Vulnerability assessments can provide useful information for the establishment of climate change adaptation strategies. We performed spatial vulnerability assessments for multiple plant species that incorporate potential range shifts to areas of future suitable climate. We conducted the assessments at a national level for plant species organized into vulnerable species groups. We then identified a climate meta-corridor for each vulnerable group that could potentially be a pathway for multiple species. 2. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…We previously used the MARS multiresponse species distribution model (SDMs) to estimate the current and the future distributions of 2,297 terrestrial plant species [27,28], of which we identified 1,031 species as CVS (Table S1) [27]. For those studies we used 65,491 species occurrence records from the South Korean second and third national ecosystem survey data (available from the ECObank: http://ecobank.nie.re.kr).…”
Section: Estimating Changes In Species Richness Under Climate Changementioning
confidence: 99%
See 3 more Smart Citations
“…We previously used the MARS multiresponse species distribution model (SDMs) to estimate the current and the future distributions of 2,297 terrestrial plant species [27,28], of which we identified 1,031 species as CVS (Table S1) [27]. For those studies we used 65,491 species occurrence records from the South Korean second and third national ecosystem survey data (available from the ECObank: http://ecobank.nie.re.kr).…”
Section: Estimating Changes In Species Richness Under Climate Changementioning
confidence: 99%
“…The MARS model was appropriate for our use because our data include large numbers of species with few records. Detailed modeling process can be found in [27,28].…”
Section: Estimating Changes In Species Richness Under Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…We used previously developed outputs from the MARS multiresponse species distribution models (SDMs) to estimate the current and the future distributions of 2,297 terrestrial plant species [19,20], of which 1,031 species have been identified as CVS (Table S1) [19]. In this study we used the species' range projections derived from the HadGEM2-ES (HE) and the NorESM1-M (NO) global climate models (GCMs) under the emission scenarios for Representative Concentration Pathways (RCP) 4.5 and RCP 8.5 [21].…”
Section: Estimating Changes In Species Richness Under Climate Changementioning
confidence: 99%